Development of Reading Abilities in Literature Lessons in the 6th Grade at Secondary Schools - Toshboyeva Munisahon Otaboy qizi (International Journal on Integrated Education, 2022)
We all recognize of vulnerable readers: secondary school pupils who shrink back from analyzing in class, lack fluency, have slender vocabularies and locate it tough to realise what they have got simply examine. These secondary school pupils have an analyzing age beneath their chronological age, and want cautious aid to enhance their analyzing cappotential. Numbers range from secondary school to secondary school, however the problems are acquainted to us.